(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article examines the significant role of religion, particularly Christianity, in shaping the social and political landscape during the 20th century, with a specific focus on its influence on the Civil Rights Movement in the United States. By exploring the intersection of faith and activism, the paper highlights how religious leaders, organizations, and theological principles shaped the ideological framework of the movement and mobilized communities for social change. The study emphasizes the spiritual and moral foundation provided by faith, contributing to the movement’s success in challenging racial injustice. The article argues that religion was not just a passive force, but an active component in the formulation of political strategies and in fostering collective action. Through the analysis of key figures and events, this paper offers a deeper understanding of the interplay between